解下列方程:(x-2)(x-3)=12 (x-2)²=(2x+3)² x²-5根号2+8=0

来源:学生作业帮助网 编辑:作业帮 时间:2024/10/05 09:14:17
解下列方程:(x-2)(x-3)=12 (x-2)²=(2x+3)² x²-5根号2+8=0
x){|O;?n+ ]#M aikh~O~O-oTm Pк|ڿH&H&(E*tM+Pf f@ چP C[3 #[]C0S tlmh@

解下列方程:(x-2)(x-3)=12 (x-2)²=(2x+3)² x²-5根号2+8=0
解下列方程:(x-2)(x-3)=12 (x-2)²=(2x+3)² x²-5根号2+8=0

解下列方程:(x-2)(x-3)=12 (x-2)²=(2x+3)² x²-5根号2+8=0
(x-2)(x-3)=12
x^2-5x+6=12
x^2-5x-6=0
(x-6)(x+1)=0
x1=6 x2=-1
(x-2)²=(2x+3)²
x-2=±(2x+3)
x-2=2x+3 或 x-2=-2x-3
-x=2+3 或 3x=-1
x1=-5 x2=-1/3
x²-5根号2+8=0
x²=8-5根号2
x=±根号(8-5根号2)